TRADITIONAL FRENCH CRAQUELINS WITH A PÂTÉ BASED ON ALTERNATIVE PROTEINS FOR A HEALTHY AND MILITARY DIETS - HELIKH, ANNA; FILON, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Ensuring humanity has access to a sufficient quantity of high-quality food is one of the most critical challenges in the contemporary world. Hunger and malnutrition, closely intertwined with inequality, have a detrimental impact on the health and development of society. Despite significant progress in food technology, these problems remain unresolved. Traditional European cuisine, with its rich diversity of regional specificities, can contribute to improving the situation. Its integration with innovative approaches, particularly the use of alternative protein sources, offers promising prospects for strengthening food security. However, despite the advantages of this approach, the use of alternative proteins in European cuisine for healthy diets has not been sufficiently investigated. To confirm the effectiveness of alternative proteins in the technology of traditional French craquelins with pâté, four samples were developed: A0 control with salmon pâté, A1 pâté with Helix pomatia, A2 pâté with Lissachatina fulica, and A3 pâté with Cornu aspersum. The study utilized alternative proteins (snails, pumpkin seed protein isolate), processed food waste (pumpkin seed protein isolate, dried sugar beet pulp), and local spices (dried horseradish). The purpose of their use is to change the level of food availability for a healthy diet. The highest protein content was found in A1 (19.61%) and A2 (18.52%). The lowest fat content was observed in A1 (13.17%) and A3 (12.98%). The chemical composition of A0 differed significantly, whereas the samples with snails had similar protein and fat content but differed in ash and moisture content. The best taste (8.9) and aftertaste (8.5) were observed in A1. The appearance (8.7) and crispness (8.6) were best in A0. The best texture (8.2) was found in A1 and A2, and aroma (8.8) in A2. The overall score was high for all samples: A1 (8.3), A2 (8.1), A0 (8.0), and A3 (7.9). The best sample was A1, but there was no significant difference from the others, indicating the effectiveness of any of the recipes. The developed packaging technology ensures food safety, long-term storage, and ease of use in combat conditions, meeting NATO requirements. Research into the wider use of food waste and local raw materials in nutrition is a pressing interdisciplinary task for specialists in food technology, cultural studies, and military science interested in developing optimal diets.